Stimulus Complexity and Mouse Strain Drive Escalation of Operant Sensation Seeking Within and Across Sessions in C57BL/6J and DBA/2J Mice - Dickson, Price E.; Mittleman, Guy (Frontiers in Behavioral Neuroscience, 2020)
Abstract Sensation seeking is a heritable trait that is genetically correlated with substance use; the shared genetic mechanisms underlying these traits are largely unknown. The relationship of sensation seeking and substance use has practical importance because discovering genes that drive sensation seeking can reveal genes driving substance use, and quantification of sensation seeking in mice is higher throughput and less technically challenging than quantification of volitional drug use. In order to fully understand the genetic mechanisms driving sensation seeking, it is critical to first understand the nongenetic factors driving sensation seeking. In the present study, we used the operant sensation seeking paradigm to assess the effects of stimulus complexity on sensation seeking in C57BL/6J and DBA/2J mice. These strains are the founders of the BXD recombinant inbred mouse panel which enables discovery of genes driving phenotypic variation. This study led to four principal conclusions. First, all sensory stimuli used in the study, regardless of complexity or number of stimulus modalities, served as reinforcers for C57BL/6J and DBA/2J mice. Second, for both C57BL/6J and DBA/2J mice, sensation seeking for a high-complexity sensory stimulus was significantly greater than sensation seeking for a low-complexity sensory stimulus. Third, for both C57BL/6J and DBA/2J mice, sensation seeking escalated significantly within-session when a multimodal sensory stimulus of medium or high complexity was used but not when a unimodal sensory stimulus of low complexity was used. Finally, both the magnitude of sensation seeking and the magnitude of within-session escalation of sensation seeking were significantly greater in mice from the DBA/2J strain relative to mice from the C57BL/6J strain. Collectively, these findings indicate that stimulus complexity and genetic background drive escalation of operant sensation seeking within and across sessions, and that the BXD recombinant inbred mouse panel can be used to discover the genetic mechanisms underlying these phenomena.